If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 13 = z * z Reorder the terms: 13 + 4x = z * z Multiply z * z 13 + 4x = z2 Solving 13 + 4x = z2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 4x = -13 + z2 Combine like terms: 13 + -13 = 0 0 + 4x = -13 + z2 4x = -13 + z2 Divide each side by '4'. x = -3.25 + 0.25z2 Simplifying x = -3.25 + 0.25z2
| -4.7-2.3y= | | X^2+4x+11=-10 | | -5/6x=7/12 | | 0.5x+0.6=0.2x-0.9 | | 3.55y-7.2y= | | 27-2x=7x | | 6b-b=56 | | 4x^4-2x^2+6=0 | | X^2-9x=29 | | (5X-7)/3=X+5 | | 2n-3[2]=53 | | -2(-2h+6)=-26 | | Y=2-6 | | (4y-2)+3y= | | (4z+2)+(y+19)=90 | | 4p^2-p+3=0 | | (3x-4)=0 | | 3(2x-1)-5=2(2x+3)+4 | | 23z-13z=15 | | 5/7x=45 | | 4x^4-2x^2+8=2 | | -(x-7)+5/3=2(x+9) | | 3x-4y=z*z | | 9+2x/9-x2=6-x | | 3a^3-18a^2+24a=0 | | 6x+25=7x | | 3x+17=8x-13 | | 5s+10c=125 | | 4y-3x=z*z | | x/7-6=-8 | | 2y^2+3y-5=4 | | n-18=-40 |